Enhanced Lipid Production in Chlamydomonas reinhardtii by Co-culturing With Azotobacter chroococcum - Xu, Lili; Cheng, Xianglong; Wang, Quanxi (Frontiers in Plant Science, 2018)
The green algae, Chlamydomonas reinhardtii, is one of thea model species used to study for research into lipid production, although research has focused on nitrogen-deficient cultures, which that inhibitions the development of biomass by C. reinhardtii and. It is the key limiting factor in lipid production by C. reinhardtii. In this study, Azotobacter chroococcum was added to the algal culture in order to improve the lipid accumulation and productivity of C. reinhardtii. The maximum lipid content and production of C. reinhardtii in the co-culture were 65.85% and 387.76 mg/L, respectively, which were 2.3-fold and 5.9 times-fold the control’s levels of 29.11% and 65.99 mg/L, respectively. The maximum lipid productivity of C. reinhardtii in the co-culture was 141.86 mg/(L•day), which was 19.4 times-fold the control’s levels of 7.33 mg/(L•day). Theose increases were attributed to the enhanced growth and, biomass and the changeed in the activity of enzymes related to lipid regulation: (ACCase, DGAT, and PDAT). Furthermore, cCompared to the conventional strategy of nitrogen deprivation, A. chroococcum added to the culture of C. reinhardtii resulteds in a higher lipid accumulation and activity, greater efficiency in the conversion of proteins to lipids, higher biomass, and increased growth of C. reinhardtii. In this wayTherefore, using A. chroococcum to improve the growth and biomass of C. reinhardtii is an efficient, rapid, and economically viable strategy for improving enhancing lipid production in the green algae C. reinhardtii.